Associations between short-term exposure to PM2.5 and cardiomyocyte injury in myocardial infarction survivors in North Carolina. Issue 1 (24th June 2022) - Wyatt, Lauren; Kamat, Gauri; Moyer, Joshua; Weaver, Anne M; Diaz-Sanchez, David; Devlin, Robert B; Di, Qian; Schwartz, Joel D; Cascio, Wayne E; Ward-Caviness, Cavin K
Abstract : Objective: Short-term ambient fine particulate matter (PM2.5 ) is associated with adverse cardiovascular events including myocardial infarction (MI). However, few studies have examined associations between PM2.5 and subclinical cardiomyocyte damage outside of overt cardiovascular events. Here we evaluate the impact of daily PM2.5 on cardiac troponin I, a cardiomyocyte specific biomarker of cellular damage. Methods: We conducted a retrospective cohort study of 2924 patients identified using electronic health records from the University of North Carolina Healthcare System who had a recorded MI between 2004 and 2016. Troponin I measurements were available from 2014 to 2016, and were required to be at least 1 week away from a clinically diagnosed MI. Daily ambient PM2.5 concentrations were estimated at 1 km resolution and assigned to patient residence. Associations between log-transformed troponin I and daily PM2.5 were evaluated using distributed lag linear mixed effects models adjusted for patient demographics, socioeconomic status and meteorology. Results: A 10 µg/m 3 elevation in PM2.5 3 days before troponin I measurement was associated with 0.06 ng/mL higher troponin I (95% CI=0.004 to 0.12). In stratified models, this association was strongest in patients that were men, white and living in less urban areas. Similar associations were observed when using 2-day rolling averages and were consistently strongest when using the average exposure over the 5 days prior to troponin I measurement. Conclusions: Daily elevations in PM2.5 were associated with damage to cardiomyocytes, outside of the occurrence of an MI. Poor air quality may cause persistent damage to the cardiovascular system leading to increased risk of cardiovascular disease and adverse cardiovascular events.